2018
DOI: 10.3390/cells7110221
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Gatekeeper: Therapeutic Targeting of Nuclear Transport

Abstract: Nuclear transport receptors of the karyopherin superfamily of proteins transport macromolecules from one compartment to the other and are critical for both cell physiology and pathophysiology. The nuclear transport machinery is tightly regulated and essential to a number of key cellular processes since the spatiotemporally expression of many proteins and the nuclear transporters themselves is crucial for cellular activities. Dysregulation of the nuclear transport machinery results in localization shifts of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 141 publications
1
75
0
Order By: Relevance
“…We found that KPNA4 silencing caused reduction of nuclear GFP NLS amounts while cytoplasmic GFP NLS levels was increased upon KPNA4 knockdown (Fig. 2b, c), suggesting KPNA4 mediates NLS-dependent nuclear imports [24].…”
Section: Kpna4 Is Required For Cellular Malignancy and Regulates Globmentioning
confidence: 79%
See 1 more Smart Citation
“…We found that KPNA4 silencing caused reduction of nuclear GFP NLS amounts while cytoplasmic GFP NLS levels was increased upon KPNA4 knockdown (Fig. 2b, c), suggesting KPNA4 mediates NLS-dependent nuclear imports [24].…”
Section: Kpna4 Is Required For Cellular Malignancy and Regulates Globmentioning
confidence: 79%
“…2a). First, we investigated NLS-dependent nuclear transport in those cells since NLSdependent nuclear import is dominantly regulated by Karyopheryin family [24]. To investigate the role of KPNA4 on nuclear import ability, GFP harboring SV40-derived NLS (GFP NLS ) was generated ( Supplementary Fig.…”
Section: Kpna4 Is Required For Cellular Malignancy and Regulates Globmentioning
confidence: 99%
“…Since the discovery of LMB, an increasing number of new inhibitors of nuclear transport mediated by importins have been reported, but all retain their persistent toxicity due to their lack of specificity. On the contrary, a limited number of inhibitors that target specific cargos have been reported (25,26). The first cargo-specific nuclear transport inhibitor described was mifepristone, a specific inhibitor of recognition of HIV-1 integrase by importin-α/β (27).…”
Section: Discussionmentioning
confidence: 99%
“…Progress in the development of drugs altering transport processes has been made. 40 Accordingly, in July 2019, the first and only nuclear export inhibitor has been approved by the FDA. The accelerated FDA approval of Selinexor (XPOVIO TM ) is based on a 25.3% response rate seen in the Phase 2b Selinexor Treatment of Refractory Myeloma (STORM) trial (NCT02336815).…”
Section: Discussionmentioning
confidence: 99%